Desain Game Matematika sebagai Instrumen Pengukur Kecerdasan Spasial untuk Siswa Sekolah Menengah Pertama - M.Mukhlas Adi Putra; Muhammad Rusdi; Syaiful Syaiful (Universitas Jambi, 2014)
The purpose of this research is to develop an instrument measuring spatial intelligence in form of mathematic game for class VII as an alternative instrument between conventional test. Research type is Development Research and using ADDIE Development Model which stands for Analyze (Analysis), Design (Design), Develop (Development), Implement (Implementation) and Evaluate (evaluation). Based on validator assessment, a developing instrument was feasible to be tested on field. Field test result show that instrument can measure student’s spatial ability as conventional test did. This instrument can be used for students with computer-use ability especially using keyboard and mouse and need further research to make a better instrument in different form from conventional instrument.